Evaluation of exposure to ionizing radiation among gamma camera operators - Agnieszka Anna Domańska; Małgorzata Bieńkiewicz; Jerzy Olszewski (Nofer Institute of Occupational Medicine, 2013)
Background: Protection of nuclear medicine unit employees from hazards of the ionizing radiation is a crucial issue of radiation protection services. We aimed to assess the severity of the occupational radiation exposure of technicians performing scintigraphic examinations at the Nuclear Medicine Department, Central Teaching Hospital of Medical University in Łódź, where thousands of different diagnostic procedures are performed yearly. Materials and Methods: In 2013 the studied diagnostic unit has employed 10 technicians, whose exposure is permanently monitored by individual dosimetry. We analyzed retrospective data of quarterly doses in terms of Hp(10) dose equivalents over the years 2001-2010. Also annual and five-year doses were determined to relate the results to current regulations. Moreover, for a selected period of one year, we collected data on the total activity of radiopharmaceuticals used for diagnostics, to analyze potential relationship with doses recorded in technicians performing the examinations. Results: In a 10-year period under study, the highest annual dose recorded in a technician was 2 mSv, which represented 10% of the annual dose limit of 20 mSv. The highest total dose for a 5-year period was 7.1 mSv, less than 10% of a 5-year dose limit for occupational exposure. Positive linear correlation was observed between total activity of radiopharmaceuticals used for diagnostics in the period of three months and respective quarterly doses received by technicians performing examinations. Conclusions: Doses received by nuclear medicine technicians performing diagnostic procedures in compliance with principles of radiation protection are low, which is confirmed by recognizing the technicians of this unit as B category employees. Med Pr 2013;64(4):503-506